Adoption of Mobile Banking Apps and their Behavioral Impacts on Millennials in Digital Age: Evidence from Developing Country Perspective - Tahira Umair; Sadia Butt (Indus Journal of Social Sciences, 2025)
This study examines the behavior of millennials generation towards benefits and services offered through mobile banking (m-Banking) applications. This study uses three different types of banking system to better understand the millennials generation views in term of customer’s loyalty (CL), positive word of mouth (WOM). Whereas, relationship quality (RQ) plays a mediation role. The benefits and services provided by m-banking channel is considered as independent variable while customer’s loyalty and positive WOM as dependent variables. Random sampling is employed to obtain data from Millennials generation, who are account holder of different conventional and Islamic banks in Pakistan. The findings of this study explored that graduate students from millennials generation have more preferred mobile banking applications as relatively compared to rest of two generation categories. Moreover, Islamic banks customers are more active to get benefits and services offered by their banks as compared to other two banking system exist in Pakistan. The overall results show significant and positive impact of m-banking applications on three categories of millennials generation. The study findings supported that benefits offered by m-banking positively relates to RQ, and RQ also positively related to positive WOM. Additionally, mediation effect of RQ was also supported